-8(6x-1)+7(7x-1)-4=4-6

Simple and best practice solution for -8(6x-1)+7(7x-1)-4=4-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(6x-1)+7(7x-1)-4=4-6 equation:


Simplifying
-8(6x + -1) + 7(7x + -1) + -4 = 4 + -6

Reorder the terms:
-8(-1 + 6x) + 7(7x + -1) + -4 = 4 + -6
(-1 * -8 + 6x * -8) + 7(7x + -1) + -4 = 4 + -6
(8 + -48x) + 7(7x + -1) + -4 = 4 + -6

Reorder the terms:
8 + -48x + 7(-1 + 7x) + -4 = 4 + -6
8 + -48x + (-1 * 7 + 7x * 7) + -4 = 4 + -6
8 + -48x + (-7 + 49x) + -4 = 4 + -6

Reorder the terms:
8 + -7 + -4 + -48x + 49x = 4 + -6

Combine like terms: 8 + -7 = 1
1 + -4 + -48x + 49x = 4 + -6

Combine like terms: 1 + -4 = -3
-3 + -48x + 49x = 4 + -6

Combine like terms: -48x + 49x = 1x
-3 + 1x = 4 + -6

Combine like terms: 4 + -6 = -2
-3 + 1x = -2

Solving
-3 + 1x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 1x = -2 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = -2 + 3
1x = -2 + 3

Combine like terms: -2 + 3 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| -7(x+1)-18=35+3 | | 16x-8(3x-2)=-24 | | 5x^3=5x^2+12 | | -8(6x+1)+7(7x-1)-4=4-6 | | 3x+46=x+2x-3 | | 5b^2+21b-20=0 | | -1/4f+20.5=12.9 | | 6x-3(3x-4)=30 | | -16+13=m-5 | | 3z+46=1+8z | | 1+1/5p=-7 | | 7x+4(-2x-5)=-31 | | -30n=-27n-57 | | -30n=-27n-57 | | 7b^2-32b-60=0 | | 6x+7-5x=13 | | 2-6p=8 | | 18.9125-(1/4) | | f(0)=-7x^2+9x+7 | | (3x-1)/4=(5x+3)/6 | | 5x+3(-7x-4)=116 | | 5i/3-9i | | 1/5(2x-4)=7 | | 15x-10(1/15+10/15x)=1 | | 4x-12=2x+30 | | -4y(8x)= | | 3g+5=7g+3 | | 6x-5=7x+6 | | 7a=33-4a | | (x+5)/3=(3x-6)/2 | | 1/3x-2/5=0 | | 1/4(7y-1)+1/8(2y+7) |

Equations solver categories